# Thread: trig problem

1. ## trig problem

Hi... I was just wondering if anyone could give me a hand with this problem. It's probably pretty simple but I can't seem to see the progression between the two lines... I'm guessing there's some use of trig identity cos^2t + sin^2t = 1... If anyone could break it down a bit further it would be much appreciated:

= -2sin^2t - cos^2t .dt

* * *

= (-1 - sin^2t).dt

2. Originally Posted by Seven7
Hi... I was just wondering if anyone could give me a hand with this problem. It's probably pretty simple but I can't seem to see the progression between the two lines... I'm guessing there's some use of trig identity cos^2t + sin^2t = 1... If anyone could break it down a bit further it would be much appreciated:

= -2sin^2t - cos^2t .dt

* * *

= (-1 - sin^2t).dt
You mean what is the (* * * )?

You are right, use that trig identity.
-2sin^2(t) is -sin^2(t) -sin^2(t), so,

the (* * *) should be:
= [-sin^2(t) -sin^2(t) -cos^2(t)]dt
= [-sin^2(t) -(sin^2(t) +cos^2(t))]dt